Triton X-114 Phase Separation of Platelet Membrane Glycoproteins from Normal Subjects and a Patient with Type I Thrombasthenia - Khanduri, U; Clark, S; Walker, I D; Chamberlain, K G; Penington, D G (Thrombosis and Haemostasis, 1986)
Surface-labelled normal and thrombasthenic platelets have been subjected to phase separation in Triton X-114. Triton-rich and Triton-poor fractions have been analysed by SDS-PAGE and IEF-SDS-PAGE. Partitioning characteristics of the major glycoproteins have been defined. The Triton-rich fraction contained GPIIb, III, IV, VI, VII, VIII, GP38 and the IIb β subunit. In contrast, the Triton-poor fraction contained the HMWGP, GPIa, Ib, IIb, III, V and GPIX.Analysis of the platelet membrane glycoproteins of a patient with Type 1 thrombasthenia has been carried out using Triton X-114. The value of the method in diagnosis of this condition and differences between our findings and those published previously are discussed.
Keywords: Platelet glycoproteins; Triton X-114 phase partitioning; Glanzmann’s thrombasthenia Type 1